Efficacy of few selected insecticides for the management of corn leaf aphid in barley - Jasrotia, Poonam; Katare, Subhash; Kashyap, Prem Lal; Kumar, Sudheer; Kharub, Ajit Singh; Singh, Gyanendra Pratap (Journal of Cereal Research, 2018)
Field trials on the evaluation of seven chemical insecticides against corn leaf aphid in barley were conducted at ICAR-Indian Institute of Wheat and Barley Research, Karnal during 2015-16 and 2016-17. To determine the efficacy of insecticides, aphid counts were made on five randomly selected plants, one day before spray and then after 1, 2, 7 and 15 days after spray. Pooled data analysis of two seasons revealed that treatments of flubendamide 480 SC @20g a.i./ha, clothianidin 50 WDG@15g a.i./ha and acetamiprid 20 SP@20g a.i./ha recorded significantly lower number of aphids; 0.5, 0.8 and 1.1 aphids/shoot after 15th days of spraying, respectively as compared to other treatments. The maximumÂ yield of 41.8 q/h was obtained in treatments of flubendamide 480 SC @20g a.i./ha and clothianidin 50 WDG@15g a.i./ha.Â Doi.org/10.25174/2249-4065/2018/83632